2009
DOI: 10.1128/cvi.00125-09
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Effect of Immune Selection on Resistance to Bactericidal Antibodies to Group B Meningococci In Vitro

Abstract: The induction of resistance by immune selective pressure to bactericidal antibodies from humans immunized with Novartis recombinant meningococcal group B vaccines was assessed. Serum bactericidal antibody titers against selected bacteria were within assay variability through a selection event frequency of 1 in 10 ؊5 . No change in antigen expression was observed by Western blotting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Results for MenACWY-CRM were consistent with those in previously published studies where participants were blinded to vaccine (16,19). However, somewhat more reactogenicity was reported than in previous studies of New Zealand OMV vaccine or preliminary results of trials of 4CMenB in adults presented at scientific meetings ( The small sample size and open-label design of this study also limit the applicability of these results to other situations and populations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results for MenACWY-CRM were consistent with those in previously published studies where participants were blinded to vaccine (16,19). However, somewhat more reactogenicity was reported than in previous studies of New Zealand OMV vaccine or preliminary results of trials of 4CMenB in adults presented at scientific meetings ( The small sample size and open-label design of this study also limit the applicability of these results to other situations and populations.…”
Section: Discussionsupporting
confidence: 88%
“…The starting dilutions in the hSBA were 1:4 for serogroups A, C, W-135, and Y and 1:2 for serogroup B strains. Methods were described previously (3,9,15,16,18,19).…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that the proteins present in the MenB vaccine are expressed throughout the in vitro growth cycle. It has also recently been shown that the level of antigen expression, and sensitivity to SBA, does not change after up to 5 rounds of selection in the presence of bactericidal antibodies generated in mice against the MenB antigens [43]. Since these proteins are important for growth and survival, they are likely to be expressed in vivo during colonization and/or infection, and indeed antibodies against NadA, fHBP and GNA2132 are present children convalescing after meningococcal disease, and antibody levels tend to increase with age [24,44,45].…”
Section: Discussionmentioning
confidence: 99%